Arthur's TV trouble - Brown, Marc Tolon (Boston : Little, Brown, 1995)
When Arthur sees advertisements for the amazing doggy Treat Timer, he decides to earn enough money to buy it for his dog Pal.
2.5
K-3
K-3.
Elem. School Library Collection
School Library Journal
Booklist
Keywords: Advertising -- Fiction; Money-making projects -- Fiction; Brothers and sisters -- Fiction; Aardvark -- Fiction; Arthur (Fictitious character : Brown) -- Fiction; Advertising -- Fiction; Money-making projects for children -- Fiction; Aardvarks -- Fiction; Siblings -- Fiction; Arthur (Fictional character : Brown) -- Fiction